THE IMPACT OF TAX AVOIDANCE AND AUDIT QUALITY ON TAX AMNESTY PROGRAM - David Pangaribuan; Amor Marundha; Mulyadi Mulyadi (Universitas Nusa Cendana, 2022)
Purpose this study was to examine the effect of tax avoidance and audit quality on companies participating in tax amnesty based on Law no. 11 of 2016 concerning Tax Amnesty. Data processing uses logistic regression. Results of study found that companies with high audit quality have a lower participating in tax amnesty. Regression results showed that the tax avoidance has no effect on companies participating in tax amnesty. Implication of the research is as initial information for government as a tax regulator in taking or formulating policies related to tax amnesty. One of conditions for receiving tax amnesty is companies regularly report their tax payments. Keywords: Tax Amnesty, Tax Avoidance, Audit Quality, Big Four